The cognizance of green computing concept and practices among secondary school students: a preliminary study - Kamarudin, Shafinah; Mohd, Siti Munirah; Zulkifli, Nurul Nadwa; Ismail, Rosli; Alan, Ribka; Lepun, Philip; Omar, Muhd Khaizer (The Science and Information Organization, 2021)
The use of information communication technology (ICT) is growing and has been a compulsory norm in society. However, the increased use of ICT facilities in all developing countries has contributed to higher energy use and lead to environmental pollution. This study explores the extent of awareness among the younger generation about green computing concepts and practices. In this study, a total of 94 secondary school students were sampled across Selangor state. The data were gathered using a set of questionnaires comprising of 20 items pertaining to the harmful effects of using computers and communication gadgets on the environment, awareness of the concepts and practices of green computing. The findings indicate it reveal that secondary school students are still not aware of the green computing concept. It is observed that 54.35% of students may not realize that computers and communication devices could be disposed of eco-safe. Furthermore, 61.96% of students do not realize that computer hardware can be recycled, and 75% of them do not have experience in disposing of their computers. Surprisingly, they mostly practice green computing when it comes to reducing energy consumption. This study contributes to determining the current level of students’ green computing awareness in a sustaining environment. In conclusion, students need to be educated on utilizing ICT resources and practicing green computing mechanisms to boost environmental sustainability.